A New Tool Improves Diagnostic Test Performance for Transmission EM Evaluation of Axonemal Dynein Arms. (August 2014) - Keith Funkhouser, W.; Niethammer, Marc; Carson, Johnny L.; Burns, Kimberlie A.; Knowles, Michael R.; Leigh, Margaret W.; Zariwala, Maimoona A.; Funkhouser, William K.
Abstract Diagnosis of primary ciliary dyskinesia (PCD) by identification of dynein arm loss in transmission electron microscopy (TEM) images can be confounded by high background noise due to random electron-dense material within the ciliary matrix, leading to diagnostic uncertainty even for experienced morphologists. The authors developed a novel image analysis tool to average the axonemal peripheral microtubular doublets, thereby increasing microtubular signal and reducing random background noise. In a randomized, double-blinded study that compared two experienced morphologists and three different diagnostic approaches, they found that use of this tool led to improvement in diagnostic TEM test performance.